Correlative Nano‐Computed Tomography and Focused Ion‐Beam Sectioning: A Case Study on a Co‐Base Superalloy Oxide Scale. Issue 9 (11th November 2019) - Lenz, Malte; Wirth, Janis; Englisch, Silvan; Rosiwal, Jan; Buchinger, Nadine; Weiser, Martin; Virtanen, Sannakaisa; Apeleo Zubiri, Benjamin; Spiecker, Erdmann
Abstract : Herein, the capabilities of a correlative tomography approach combining laboratory nano X‐ray computed tomography, focused ion‐beam sectioning, and energy‐dispersive X‐ray spectroscopy are utilized for the characterization of multilayered oxide scales of Co‐base superalloys regarding their 3D morphology and chemical composition. The combination of complementary 3D imaging techniques allows for a precise and reliable segmentation of the pore space, oxide precipitates, and different phases of the initial material. Such information is instrumental to a microscopic understanding of oxidation in this new class of superalloys and key to improvement of oxidation resistance in the next‐generation high‐temperature materials. Abstract : The capabilities of a correlative tomography approach combining nano‐computed tomography (CT), focused ion beam (FIB) sectioning, and energy‐dispersive X‐ray spectroscopy (EDXS) are utilized for the 3D characterization of multilayered oxide scales of Co‐base superalloys. The combination enables segmentation of porosity, oxide precipitates, and other phases, which is instrumental to a microscopic understanding of oxidation and improvement of oxidation resistance.